A fast and effective determination of the biodistribution and subcellular localization of fluorescent immunoliposomes in freshly excised animal organs - Tansi, Felista L. (BMC Biotechnol, 2017)
BACKGROUND: Preclinical research implementing fluorescence-based approaches is inevitable for drug discovery and technology. For example, a variety of contrast agents developed for biomedical imaging are usually evaluated in cell systems and animal models based on their conjugation to fluorescent dyes. Biodistribution studies of excised organs are often performed by macroscopic imaging, whereas the subcellular localization though vital, is often neglected or further validated by histological procedures. Available systems used to define the subcellular biodistribution of contrast agents such as intravital microscopes or ex vivo histological analysis are expensive and not affordable by the majority of researchers, or encompass tedious and time consuming steps that may modify the contrast agents and falsify the results. Thus, affordable and more reliable approaches to study the biodistribution of contrast agents are required. We developed fluorescent immunoliposomes specific for human fibroblast activation protein and murine endoglin, and used macroscopic fluorescence imaging and confocal microscopy to determine their biodistribution and subcellular localization in freshly excised mice organs at different time points post intravenous injection. RESULTS: Near infrared fluorescence macroscopic imaging revealed key differences in the biodistribution of the respective immunoliposomes at different time points post injection, which correlated to the first-pass effect as well as the binding of the probes to molecular targets within the mice organs. Thus, a higher accumulation and longer retention of the murine endoglin immunoliposomes was seen in the lungs, liver and kidneys than the FAP specific immunoliposomes. Confocal microscopy showed that tissue autofluorescence enables detection of organ morphology and cellular components within freshly excised, non-processed organs, and that fluorescent probes with absorption and emission maxima beyond the tissue autofluorescence range can be easily distinguished. Hence, the endoglin targeting immunoliposomes retained in some organs could be detected in the vascular endothelia cells of the organs. CONCLUSIONS: The underlying work represents a quick, effective and more reliable setup to validate the macroscopic and subcellular biodistribution of contrast agents in freshly excised animal organs. The approach will be highly beneficial to many researchers involved in nanodrug design or in fluorescence-based studies on disease pathogenesis.